Assessing scientific merit through data quality in a domain repository (PUBMET, 2025)
A widespread open science publishing culture means the researchers involved should be rewarded for the merit contained in the research output they produce and share. A recent survey shows that “Open and FAIR data management and sharing” is the most deserving of reward. (Grattarola et al., 2024). Research assessment should prioritize quality, encompassing the entire spectrum of research outputs, including research data, computer code, and other. Evaluating the scientific quality of research data is crucial for including it as a legitimate scientific output, akin to the way literature is evaluated in the editorial and peer review publishing selection.
Keywords: data repository; data curation; research data quality; research assessment; re-use